2023
DOI: 10.1002/pc.27225
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the mechanical properties of fiber metal laminate by surface treatment

Abstract: Fiber‐metal laminates with high toughness and high strength have become an important direction for the development of new materials in the future. During the production and service process of fiber‐metal laminates, brittle fracture and interlaminate damage are easily caused by low load, which leads to the instability and damage to the overall structure. This article mainly studies the effects of surface treatment process, and material combination on the mechanical properties of glass fiber/polypropylene (PP)/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…. Zou et al introduced polar functional groups into the nonpolar chain of polypropylene through grafting reaction and subjected the stainless steel mesh in GF/PP/SSM laminates to surface decay and phosphorus treatment, thereby improving the bonding strength between metal and stainless steel. Zhang et al designed poly­[glycidyl methacrylate- co -( N -(3,4-dihydroxyphenethyl)­methacrylamide] [P­(GMA- co -DOMAm)] shown in Figure a.…”
Section: Surface Treatment Methods Of Resinmentioning
confidence: 99%
“…. Zou et al introduced polar functional groups into the nonpolar chain of polypropylene through grafting reaction and subjected the stainless steel mesh in GF/PP/SSM laminates to surface decay and phosphorus treatment, thereby improving the bonding strength between metal and stainless steel. Zhang et al designed poly­[glycidyl methacrylate- co -( N -(3,4-dihydroxyphenethyl)­methacrylamide] [P­(GMA- co -DOMAm)] shown in Figure a.…”
Section: Surface Treatment Methods Of Resinmentioning
confidence: 99%
“…Zhu et al found that coupling agent A‐1387 has better wettability on the surface of aluminum alloy, which contributes greatly to the improvement of interface structure and properties 9 . Zou et al used etched and phosphatized stainless steel mesh to enhance the interface bonding effect with PP‐g‐MAH, thereby improving the overall structural strength of the laminate 10 . Feng et al used nanosecond laser to treat the Al alloy plate surface and improved the bonding joint of Al alloy and thermoplastic carbon fiber composite material 11 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Zou et al used etched and phosphatized stainless steel mesh to enhance the interface bonding effect with PPg-MAH, thereby improving the overall structural strength of the laminate. 10 Feng et al used nanosecond laser to treat the Al alloy plate surface and improved the bonding joint of Al alloy and thermoplastic carbon fiber composite material. 11 Ye et al anodized titanium sheet and formed TiO 2 nanotube array on the surface of the titanium sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Research has been oriented towards enhancing metal-FRP composite interfacial adhesion by pre-treating the metal surface via mechanical abrasion, alkaline degassing, acid etching, anodizing, and plasma treatment. [11][12][13] Sinmazçelik et al 14 reviewed various surface treatment techniques and amongst these methods, acid etching is considered a simple and efficient method, which can remove the weak native oxide layer on the metal surface and create a microporous/nanoporous surface with high roughness to enhance the interfacial adhesion with the polymer matrix. Various works have reported increments in the mechanical properties of FMLs/bonded joints in the range of $16% to $74% after acid etching.…”
Section: Introductionmentioning
confidence: 99%
“…In FMLs, the issue of delamination is exacerbated due to the introduction of a new interface between the metal and the FRP composite plies which is highly susceptible to delamination. Research has been oriented towards enhancing metal‐FRP composite interfacial adhesion by pre‐treating the metal surface via mechanical abrasion, alkaline degassing, acid etching, anodizing, and plasma treatment 11–13 . Sinmazçelik et al 14 reviewed various surface treatment techniques and amongst these methods, acid etching is considered a simple and efficient method, which can remove the weak native oxide layer on the metal surface and create a microporous/nanoporous surface with high roughness to enhance the interfacial adhesion with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%